PYROMETALLURGICAL METHOD FOR THE RECOVERY OF ALUMINUM FROM Fe2O3/α-Al2O3 CATALYST - Djerad, Souad (MATTER: International Journal of Science and Technology, 2017)
In this study we report an investigation on the recovery of iron and aluminum oxides by roasting Fe2O3/Al2O3 catalyst with KHSO4 under different operation conditions such as temperature, KHSO4/catalyst mass ratio (K/C) and reaction time. It was found that 79.67% of Al2O3 and 96.94% of Fe2O3 were dissolved after 7h at 600°C and K/C= 36. After the separation of Fe(III) and Al(III) in aqueous solution by a pH-controlled precipitation method, the resulting Al(OH)3 was dehydrated to γ-AlOOH (pseudo-boehmite) by heating at 105°C while γ- η and α-Al2O3+θ residues were obtained after calcination at 500-950 and 1200°C respectively.